Studi Perbandingan Hukum “Plea Bargaining System” di Amerika Serikat dengan “Jalur Khusus” di Indonesia - Rifi Hermawati (CV Rewang Rencang, 2023)
Plea Bargaining developed in the United States of America. It is a negotiation between the public prosecutor and the accused or their defender so that the process of resolving criminal cases is carried out quickly and effectively. Plea Bargaining became the basis for the formation of the concept of “special lane” in Indonesia in article 199 of the Criminal Procedure Code Bill. Both of these concepts carry the short examination mechanism. The difference is in the